1991
DOI: 10.1182/blood.v78.3.688.bloodjournal783688
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone exerts a depressive influence on the production of interleukin-4 (IL-4), IL-5, and gamma-interferon, but not IL-2 by activated murine T cells

Abstract: The present study examined the effects of the androgen steroid, dihydrotestosterone (DHT), on murine T-cell production of a number of lymphokines. Direct exposure of murine T cells to DHT in vitro was found to reduce the amount of interleukin-4 (IL-4), IL-5, and gamma- interferon (gamma IFN) produced after activation with anti-CD3 without affecting the production of IL-2. Exposure of T cells to either androstenedione or testosterone (the metabolic precursors of DHT) affected no change in the biosynthesis of ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 0 publications
4
60
0
3
Order By: Relevance
“…Moreover, in accordance with our previous study 8 we found no differences in IFN‐ γ production by both Th and Tc lymphocytes between untreated samples and samples treated with testosterone. This is in line with results from Araneo et al who also showed no changes in synthesis of IFN‐ γ and IL‐2 by murine T cells exposed to testosterone 14 …”
Section: Discussionsupporting
confidence: 92%
“…Moreover, in accordance with our previous study 8 we found no differences in IFN‐ γ production by both Th and Tc lymphocytes between untreated samples and samples treated with testosterone. This is in line with results from Araneo et al who also showed no changes in synthesis of IFN‐ γ and IL‐2 by murine T cells exposed to testosterone 14 …”
Section: Discussionsupporting
confidence: 92%
“…One might anticipate, however, that effects of maternal testosterone on the cytokine milieu would be more pronounced in the absence of maternal atopic disease, as maternoplacental cytokine production is likely to be less markedly Th2 skewed and over‐riding in this situation, and this is what we found. Support for a downregulating effect of testosterone on Th2 cytokines comes from studies of adult mice which have shown that DHEA in vivo , and the metabolite of testosterone, dihydrotestosterone, in vitro , reduce levels and expression of interleukin (IL)‐4, IL‐5, IL‐6 and IL‐10 (11, 12, 40, 41). Data are conflicting on the effects of these androgens on the Th1 cytokines interferon‐ γ and IL‐2 (12, 40, 41).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a high level of IL‐4 production is reported in androgen resistance [48]. It has also been shown that dihydrotestosterone exerts a depressive effect on the production of IL‐4 by activated murine T cells [49]. IL‐2 is a mediator produced chiefly by the Th1 subset of helper/inducer T cells and stimulates other T cells, while IL‐4 is produced by Th2 cells and targeted to T and B cells.…”
Section: Discussionmentioning
confidence: 99%